2009
DOI: 10.1038/mt.2009.70
|View full text |Cite
|
Sign up to set email alerts
|

VEGF Gene Therapy Fails to Improve Perfusion of Ischemic Myocardium in Patients With Advanced Coronary Disease: Results of the NORTHERN Trial

Abstract: Despite the promise of proangiogenic gene therapy most clinical trials have failed to show benefit for the primary end point analysis. The NOGA angiogenesis Revascularization Therapy: assessment by RadioNuclide imaging (NORTHERN) trial was a double-blind, placebo-controlled study of intramyocardial vascular endothelial growth factor (VEGF165) gene therapy versus placebo, involving seven sites across Canada, designed to overcome major limitations of previous proangiogenic gene therapy trials. A total of 93 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
165
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(169 citation statements)
references
References 31 publications
3
165
0
1
Order By: Relevance
“…Other authors have reported the safety procedures [19][20][21]. However, this information is important because it was done in our midst and with technical peculiarities of the surgical procedure, and, previously, only assays were performed in Brazil [23,24].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Other authors have reported the safety procedures [19][20][21]. However, this information is important because it was done in our midst and with technical peculiarities of the surgical procedure, and, previously, only assays were performed in Brazil [23,24].…”
Section: Discussionmentioning
confidence: 98%
“…The vascular endothelial growth factor (vascular endothelial growth factor -VEGF) has been the focus of several studies [5,6] and its effects are being tested in patients with severe CAD [7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Studies use different doses, vectors and ways Conclusions: The therapy has proved to be safe and feasible in this series of patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, phase II/III studies did not confirm these initial results. 90 Endothelium-specific vectors can also be an alternative to liver-and muscle-specific vectors for systemic expression. Both natural (vWF, FLT-1 and ICAM-2) and synthetic promoters have been used to drive endothelium-specific expression by viral and nonviral vectors.…”
Section: Endotheliummentioning
confidence: 99%
“…We also noted an improved cardiac functions as assessed by echocardiography. However, our interest shifted from VEGF to the molecules downstream of VEGF that may be involved in angiogenesis after clinical trials of VEGF failed to yield similar outcomes in patients with cardiovascular disease 5, 6, 7…”
Section: Introductionmentioning
confidence: 99%